Replication Data for: Length-weight relationship and condition factor for Prochilodus lineatus, an important commercial fish, in contrasting water-quality environments of the middle Tietê River basin, Southeast Brazil - Quirici Urbanski, Bruna (2023)
This work was carried out with the objective of evaluating the length-weight relationship (LWR), the allometric condition factor (Ka), as well as its correlation with limnological variables for Prochilodus lineatus from the middle Tietê River basin. Fish were collected using gill nets, between December 2016 and October 2019, in two rivers with contrasting environmental conditions, totaling 46 specimens in the highly polluted Tietê River, and 37 in the Peixe River, a relatively well-conserved tributary. Environmental measures were obtained concomitantly to the fish captures. The results showed an isometric growth (b=3.00) for the fish from the Tietê River and a positive allometric growth (b=3.23) for the fish from the Peixe River. The mean value of Ka was, unexpectedly, higher for the main river (Ka=2.63) when compared to its tributary (Ka=2.42), being statistically different from each other. This can be explained by the much higher availability of organic sediments in the main river, resulting from a long-term eutrophication process. Nevertheless, the positive and statistically significant correlations with dissolved oxygen, for both rivers, as well as the negative correlation with electric conductivity for Tietê River, indicate the negative effects of the water quality deterioration on the fish condition factor. Results indicated that P. lineatus, even in a poor-quality environment is capable to maintain good growth rates. The work contributes to the expansion of knowledge about P. lineatus, the fish of higher commercial interest for the anglers of the middle Tietê River basin, which is severely impacted by unsustainable human actions.